2022
DOI: 10.1186/s12889-022-12774-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration and sleep quality with overweight/obesity among adolescents of Bangladesh: a multilevel analysis

Abstract: Background Sleep deprivation is widely recognized as a potential contributor to childhood obesity. However, few studies have addressed this issue in low-income settings. The aim of this study was to determine the association of both sleep duration and sleep quality with overweight/obesity among adolescents of Bangladesh. Methods A cross-sectional study was conducted in four randomly selected schools in Gazipur, Bangladesh, from May to August 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(49 reference statements)
2
6
0
Order By: Relevance
“…This points to the necessity of a healthy and balanced diet at an early age rather than calorie-dense food to increase body weight. Sleeping <8 h per day was significantly associated with lower odds of being underweight, which is supported by other studies (29,30). Lack of physical activities was significantly associated with overweight and obesity.…”
Section: Discussionsupporting
confidence: 82%
“…This points to the necessity of a healthy and balanced diet at an early age rather than calorie-dense food to increase body weight. Sleeping <8 h per day was significantly associated with lower odds of being underweight, which is supported by other studies (29,30). Lack of physical activities was significantly associated with overweight and obesity.…”
Section: Discussionsupporting
confidence: 82%
“…The BMI values for different age categories in the present study were smaller than similar studies conducted in Bangladesh and India. 15,16 Observed results were found to be similar in a study conducted among vegetarian and non-vegetarian Nepalese children. 17 According to World Health Organization's (WHO) growth reference for 5-19 years, the students participated in the present study found to be underweight.…”
Section: Body Surface Area (Bsa) Of Boys and Girls Of Government Prim...supporting
confidence: 69%
“…Therefore, ensuring sufficient sleep may act as an effective technique for preventing obesity throughout the developmental phases. 25 In a previous study, it was observed that children with a delayed bedtime and wake-up time had a notable elevation in their BMI in comparison to those with an earlier bedtime and wake-up time, despite both groups having equivalent sleep durations. 26 It was observed that the scores for the responses improved after the intervention.…”
Section: Discussionmentioning
confidence: 93%